2019
DOI: 10.4467/2353737xct.19.126.11451
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological aspects of the use of parabens in the production of cosmetics

Abstract: Parabens are synthetic preservatives that are used on a large scale in the cosmetics, pharmaceutical and food industries. Their task is primarily to prolong the shelf life of selected products-cosmetics, medicines or food-by maintaining their microbiological purity. Parabens protect products against deterioration and microorganisms, extending their durability by up to several months without interfering with their composition and operation. Parabens do not change the aroma, taste, density or other characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 82 publications
(99 reference statements)
0
2
0
2
Order By: Relevance
“…Tujuan penambahan paraben adalah untuk mencegah tumbuhnya bakteri maupun jamur pada kosmetik. Namun, penggunaan paraben sering dikaitkan dengan permasalahan alergi, obesitas, dan infertilitas (Barabasz et al, 2019) Disamping itu, bahan pewangi atau fragrance akhir-akhir ini juga semakin massif ditambahkan pada produk kosmetik selain untuk meningkatkan aroma juga berperan untuk memposisikan produk diantara produk lainnya. Salah satu bahan pewangi sintetik yang sering digunakan pada produk kosmetik seperti shampoo, body lotion, sabun mandi, detergen adalah polyethylene terephthalate (Becker et al, 2014).…”
Section: Pendahuluanunclassified
“…Tujuan penambahan paraben adalah untuk mencegah tumbuhnya bakteri maupun jamur pada kosmetik. Namun, penggunaan paraben sering dikaitkan dengan permasalahan alergi, obesitas, dan infertilitas (Barabasz et al, 2019) Disamping itu, bahan pewangi atau fragrance akhir-akhir ini juga semakin massif ditambahkan pada produk kosmetik selain untuk meningkatkan aroma juga berperan untuk memposisikan produk diantara produk lainnya. Salah satu bahan pewangi sintetik yang sering digunakan pada produk kosmetik seperti shampoo, body lotion, sabun mandi, detergen adalah polyethylene terephthalate (Becker et al, 2014).…”
Section: Pendahuluanunclassified
“…Subsequently, dioxygenase enzymes cleave the aromatic ring, initiating degradation and production of β-ketoadipate. Further reactions lead to the formation of acetyl-CoA and succinate, which participate in the TCA cycle to generate ATP (Barabasz et al, 2019) and alcohol. Esterases are the primary enzymes involved in this initial stage.…”
Section: Source-pcpmentioning
confidence: 99%
“…They were first used in medicine in 1920 and first discovered to have estrogenic activity in 1998 . In the decades that followed, studies have found that PBs can cause skin diseases , and affect the development of reproductive organs, as well as lead to disorders of thyroid hormone levels, obesity, , premature birth, weight loss, and hyperactivity of newborns . The potential risk of exposure to PBs and its impact on human health has attracted increasing attention.…”
Section: Introductionmentioning
confidence: 99%